2011
DOI: 10.1096/fasebj.25.1_supplement.915.15
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lipid metabolism in interacting visceral adipocytes and ovarian cancer cells

Abstract: Ovarian cancer (OvCa) is the 5th leading cause of cancer‐related deaths in women. The primary site of OvCa metastasis is the adipocyte (ADI)‐dominated omentum. A growing body of evidence supports metabolic dysregulation as a cancer hallmark. This research was aimed at investigating metabolic changes in interacting OvCa cells and ADIs. Human omental ADIs were plated on OvCa cells for coculture experiments and protein detection. Fatty acid (FA) oxidation was assessed by radioisotopic assay. FA binding protein 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…According to a previous review [24], most HGSOCs are usually diagnosed at an advanced stage and have a poor prognosis, similar to our study. Nieman et al [25] showed that 80% of patients with HGSOC presented with omental metastasis, similar to our study, which demonstrated that 83.3% of patients with HGSOC had omental metastasis. In addition, we found that omental metastasis was a significant pathological factor for predicting the p53 overexpression pattern in HGSOC (87.8% vs.…”
Section: Discussionsupporting
confidence: 91%
“…According to a previous review [24], most HGSOCs are usually diagnosed at an advanced stage and have a poor prognosis, similar to our study. Nieman et al [25] showed that 80% of patients with HGSOC presented with omental metastasis, similar to our study, which demonstrated that 83.3% of patients with HGSOC had omental metastasis. In addition, we found that omental metastasis was a significant pathological factor for predicting the p53 overexpression pattern in HGSOC (87.8% vs.…”
Section: Discussionsupporting
confidence: 91%
“…Secreted factors from the omentum have been shown to act as chemotactic factors that attract OC cells to this organ. Upon arrival, omental adipocytes have been shown to modulate OC cancer proliferation, metabolism, and response to chemotherapy (9,66,67). Given that OC mostly metastasizes via the trans-coelomic route and is mainly contained within the peritoneal cavity, the demonstration that adipose-derived exosomal miRNA can modulate epigenetic regulators in OC cells show that these cancer cells do not need to be in direct contact with adipocytes and can be located anywhere in the peritoneal cavity to be re-programmed by this microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is a central component of the cancer microenvironment (4), and is made up mostly of adipocytes and to a lesser extent, endothelial cells, and macrophages (5). Factors secreted by adipocytes as well as direct adipocyte-cancer cell interaction have been shown to support tumor progression in various cancer types including, breast, ovarian, prostate, and colon cancers (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…High-grade serous ovarian carcinoma is the most common subtype of ovarian cancer, often diagnosed at an advanced stage with 10-year survival of 15% (1). Nearly 80% of the HGSC metastasize to omentum, a large fat tissue covering stomach and intestine, which provides metabolic and inflammatory microenvironment for cancer and immune cells (2). The standard of care for HGSC includes primary debulking surgery followed by platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%